CRITICAL DISCOURSE ANALYSIS AT INSTAGRAM’S CAPTION IN ADVERTISEMENT OF PONDS - Lucia Putri; Diana Rozelin; Chandri Febri Santi (Nazharat: Jurnal Kebudayaan, 2020)
Critical discourse analysis (CDA) provides theories and methods for the empirical study of the relations between discourse and social and cultural developments in different social domains. CDA is not only a description and interpretation of discourse in context, but also offers an explanation of why and how discourses work. The writer interests in discussing Critical discourse analysis (CDA) because by using the critical discourse analysis (cda) this can express how community ideology about an event. The aims of the research are : (1) to elaborate of textual features of the advertisement, (2) to find out of discursive thecnique of the advertisement, (3) to find out social feature of the adevertisement. In this research, the writer applies the theory of Fairclough with three dimensional models by as supporting theory to answer the problem of the research. This research is qualitative research that focused on qualitative research by Hill Way in Kaelan and uses technique purposive sampling by Sugiyono. The writer found on the research that: (1) there are four textual features in the advertisement, (2) the tecniques of discursive found in the advertisement are two tecniques, with celebrity endorsement and scientific evindence, (3) to know how ideology and consumers views of this advertisement